Bio-sorption for tannery effluent treatment using eggshell wastes; kinetics, isotherm and thermodynamic study - El-Sayed R.E. Hassan; Merit Rostom; Fatma E. Farghaly; M.A. Abdel Khalek (Egyptian Journal of Petroleum)
Since, cobalt, zinc, mercury and lead ions are high toxic heavy metals; this work aims to investigate the efficiency of eggshell as a low cost sorbent for their ions from aqueous solution. Adsorption of heavy metals on surfaces of eggshell obeyed second order kinetics. Adsorption isotherm belonged to Freundlich model and displayed multilayer adsorption. The maximum adsorption capacity was estimated as 204, 153, 121 and 98 mg/g for Co3+, Zn2+, Hg2+ and Pb2+ respectively. The values of free energy of adsorption evidenced the physical adsorption occurrence. It is demonstrated that eggshell, as an industrial waste, was efficiently used as an adsorbent for wastewater treatment. Eggshells powder removed efficiently heavy metal ions from a tannery wastewater and removal efficiency reached up to 99%.